The Influence Of Content Marketing Factors Towards Actual Visit Behavior Through Behavioral Intention - Jovan, Jovan; Ronald, Ronald (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2022)
The purpose of this research is to see the influence of content marketing factors towards actual visit behavior through behavioral intention to visit at Pepper Lunch Medan. This study is causal research. The method used is quantitative methods of processing the data using AMOS. Data was collected by distributing questionnaires to 150 respondents with the characteristics of male and female respondents aged 18-60 years, have visited Pepper Lunch Medan once in the last 2 years and follow or have seen Instagram of Pepper Lunch Medan. The results of this research shows that Experiencing Appeal has a positive but not significant effect to Customer’s Behavioral Intention to Visit and the other 5 hypothesis have positive and significant effect